Antimony (IV) Oxide Nanorods/Reduced Graphene Oxide as the Anode Material of Sodium-ion Batteries with Excellent Electrochemical Performance. (20th June 2017) - Wang, Gui-Zhi; Feng, Jian-Min; Dong, Lei; Li, Xi-Fei; Li, De-Jun
Graphical abstract: Nanocomposites of Sb2 O4 /RGO with the structure of Sb2 O4 nanorods uniform anchored on graphene were synthesized through a simple liquid composing process for the first time. The research explored different ratio of Sb2 O4 and RGO and the Sb2 O4 /RGO-II composite exhibited best electrochemical performance for sodium-ion battery with a stable sodium-ion storage capacity of 551 ± 5 mAh g −1 after 100 cycles and an excellent rate performance of 401 ± 5 mAh g −1 at 1 A g −1 . Highlights: Sb2 O4 /RGO is successfully prepared by one-step solvothermal process. The composite is with the structure of Sb2 O4 nanorods uniformly anchored on graphene. Sb2 O4 /RGO composite exhibits talent cycle stability and rate capability for sodium-ion battery. Abstract: Sodium-ion batteries (SIBs) have attracted lots of significant interests, arising from in regard to the development of developing a low-cost energy storage system for renewable energy. Antimony-based materials with that have high theoretical storage capacities of Na + have become one of the most focused SIB anode materials. Among of which, Sb2 O4 has a higher and thus superior Na + storage capacity of 1227 mAh g −1 compared to other antinomy-based materials. In this work, one simple solvothermal process has been developed to prepare Sb2 O4 /reduced graphene oxide (Sb2 O4 /RGO) composites with a nanostructure of Sb2 O4 nanorods anchored on RGO. Sb2 O4 /RGO shows an obviously enhanced electrochemical performance with an initial Na + storage capacity of 842 ± 5 mAh g −1, a rechargeable capacity of 551 ± 5 mAh g −1 at 50 mA g −1 after 100 cycles and an excellent rate performance of 401 ± 5 mAh g −1 at 1 A g −1 .